A Relative Importance Index Approach to On-Site Building Construction Workers’ Perception of Occupational Hazards Assessment - Boakye, Maxwell; Adanu, Selase Kofi; Adu-Gyamfi, Christopher; Asare, Richard Kwadzo; Asantewaa-Tannor, Patricia; Ayimah, John Coker; Agbosu, Worlanyo Kwabena (La Medicina del Lavoro, 2023)
Background: The construction industry has a percentage of work-related injuries and fatalities. Workers’ perception of occupational hazards exposure can be a proactive management tool in knowing the state of construction site safety performance. This study aimed to assess the hazard perception of on-site construction workers in Ghana. Methods: Using a structured questionnaire, data was collected from 197 construction workers at live building sites in the Ho Municipality. The data were analyzed using the Relative Importance Index (RII) approach. Results: The study revealed that on-site construction workers perceived ergonomic hazards as the most frequent, followed by physical, phycological, biological, and chemical hazards. The importance level of RII revealed that long working hours and bending or twisting back during task performance were perceived as the most severe hazards. Long working hours had the highest overall RII ranking, followed by bending or twisting back during task performance, manual lifting of objects or loads, scorching temperatures, and lengthy standing for prolonged periods. Conclusions: Given the adverse health effects of working for long hours, the management of Ghanaian construction industries needs to reinforce the legislation on working hours to safeguard workers’ occupational health. Safety professionals can use the study’s findings to improve safety performance in the Ghanaian construction industry.